IOT- enabled hydroponic farming: a solution for high-temperature regions - Chua, Shi Jian (2024)
This project focuses on the development of an IoT-enabled hydroponic system designed to mitigate the effects of high ambient temperatures on plant growth and maintain optimal growing conditions, particularly in high temperature regions like Malaysia. By utilizing a Deep Water Culture (DWC) hydroponic method, the system integrates sensors to monitor critical environmental parameters such as temperature, humidity, pH, and Total Dissolved Solids (TDS), ensuring optimal plant growing condition. A fogger system was implemented to reduce temperature stress on plants during peak heat conditions. Experimental results demonstrated that the fogger system significantly improved the growth of lettuce plants, as evidenced by greater plant height and larger leaf area compared to those grown without the fogger cooling mechanism.